The Process Of Marketing Religious Broadcasting By The Public Broadcasting Agency Of The Republic Of Indonesia Television (Tvri) To Enhance The Role Of The Prime Minister In The Era Of New Media - Putri Rahmadani Zein; Rubino Rubino; Efi Brata Madya (UNIVERSITAS PAKUAN, 2023)
This research aims to understand the marketing process of religious broadcasting by the public broadcaster Television of the Republic of Indonesia (TVRI) to increase viewers’ interest in the new media era. This research is field research with a qualitative descriptive approach. Data is collected through interviews, observations, and documentation. Data analysis is done by reducing data, presenting it, and performing verification. To maintain the authenticity of the data, researchers use triangulation techniques and perform information verification through member checks. The results of this study show that TVRI North Sumatra increases viewers’ interest in the new media era by modifying religious broadcasts and attractively packaging them. Choosing an interesting and relevant discussion topic is also an essential factor. However, competition with other television stations and a lack of promotion on religious broadcasts became a barrier. TVRI leverages new media such as apps, websites, and YouTube accounts to reach and interact with viewers more effectively.